EDUKASI FLASHCARD KARTUPASTING SEBAGAI MEDIA KAMPANYE PENCEGAHAN STUNTING - Malayati, Robi'ah Machtumah; Mughiroh, Ainun Fitri; Anwari; Slamet, Moh.; as'ad, muhammad (ABIDUMASY, 2024)
Stunting remains a significant public health issue in Indonesia, with a national prevalence of 21.6%. The government aims to reduce this rate to 14% by 2024, as outlined in Presidential Regulation No. 72 of 2021. In Jombang Regency, 5,113 children were identified as stunted in 2023, including those in Gondek Village, Mojowarno District. Despite government efforts, many parents in Bangunrejo Hamlet lack awareness of stunting and resist guidance from health workers. This community service program aims to address this challenge by educating the public through KARTUPASTing (Anti-Stunting Smart Cards), a creative flashcard tool designed to increase awareness of stunting prevention. KARTUPASTing has received recognition, winning third place in the 2024 KRENOVA (Creativity and Innovation) competition in Jombang. The program involves community education, training, and ongoing support, ensuring active participation from mothers and families with children aged 0-23 months. Regular evaluations will be conducted to measure the program's impact, with the goal of ensuring its sustainability. This initiative also aligns with the Merdeka Belajar Kampus Merdeka (MBKM) program, allowing students to actively contribute to community engagement efforts